Calibration of beam position monitors for high energy accelerators based on average trajectories - Cardona, Javier Fernando (2021)
This article presents a method that uses turn-by-turn beam position data and k-modulation data to measure the calibration factors of beam position monitors in high energy accelerators. In this method, new algorithms have been developed to reduce the effect of coupling and other sources of uncertainty, allowing accurate estimates of the calibration factors. Simulations with known sources of errors indicate that calibration factors can be recovered with an accuracy of 0.7% rms for arc beam position monitors and an accuracy of 0.4% rms for interaction region beam position monitors. The calibration factors are also obtained from LHC experimental data and are used to evaluate the effect this calibration has on a quadrupole correction estimated with the action and phase jump method for a interaction region of the LHC.